Pseudanthias vizagensis, a junior synonym of Pseudanthias pillai Heemstra & Akhilesh, 2012 (Perciformes: Serranidae) - Akhilesh, K.v.; Kishore, T.g.; Muktha, M.; Lisher, M.w.; Ambarish, Gop P.; Anulekshmi, C. (Zootaxa, 2020)
Pseudanthias vizagensis Krishna, Rao and Venu, 2017 was described from 44 specimens, collected from Visakhapatnam (Andhra Pradesh), on the Bay of Bengal coast of India, but without clear designation of a holotype. The characters used for differentiating the species from its nearest congener Pseudanthias pillai Heemstra & Akhilesh, 2012, a species currently known only from the northern Indian Ocean, were limited, poor and substantially overlapping. Examination of additional material of P. pillai from the Arabian Sea, Bay of Bengal, Andaman Sea, and comparison with the original description and images of P. vizagensis revealed that the latter is a junior synonym of P. pillai. Diagnostic characters are reviewed, additional morphological details and fresh colouration, including sexual dimorphic characters not covered in previous works are provided.